The Influence of Human Resource Competence and Information Technology Utilization on the Quality of Financial Reports (Study on Regional Office XI of the State Civil Service Agency) - Rottie, Anggrainy Atletika; Sendouw, Recky; Tarore, Steven Vleike (Technium Social Sciences Journal, 2025)
This study aims to determine how much influence Human Resources Competence (X1) and Information Technology Utilization (X2) have on the Quality of Financial Reports (Y) both partially and simultaneously. This research was conducted at the Regional Office XI of the Manado State Civil Service Agency, the technique of distributing questionnaires using google forms distributed to 89 employees at the Regional Office XI of the State Civil Service Agency. Data analysis was carried out by testing variant-based Partial Least Square (PLS) or components of the Structural Equation Modeling (SEM) approach and testing the effect of independent variables on the dependent variable with the smart-PLS program, but the Classical Assumption Test was still carried out with the SPSS program. The results showed that Human Resources Competence and Information Technology Utilization both partially and simultaneously had a significant effect on the Quality of Financial Reports of Regional Office XI of the Manado State Civil Service Agency. The results of the coefficient of determination (R2) show 0.587, meaning that the variables of HR competence and utilization of information technology as predictor variables simultaneously have an influence of 58.7% on the quality of financial reports. Through the results of the research that has been done, it is recommended to carry out continuous human resource development and optimization of information technology by updating infrastructure.